“I ♥ Boobies! (Keep A Breast)” Bracelets: What’s your policy? - Robert Hachiya (The Advocate, 2014)
The United States Supreme Court has been asked to review a 2013 Third Circuit Court of Appeals reling against a Pennsylvania school district that disciplined students for wearing “I love Boobies! (Keep A Breast)” bracelets. This article reviews litigation related to the effort by schools to regulate bracelets and associated student freedom of expression concerns. School administrators concerned with regulating the bracelets are offered policy suggestions.